Boosting the Photocurrent in BiFeO3 Thin Films via a Domain‐Wall‐Defect Interaction. Issue 1 (11th September 2022) - Zhang, Hang-Bo; Yang, Ming-Min; Alexe, Marin
Abstract : Ferroelectric domain walls are of great interest due to their nontrivial electronic properties. Herein, a large photocurrent is detected only in the stripe domain structure of BiFeO3 thin films. By the temperature‐resolved time‐dependent photocurrent measurements, the significant trapping effect is revealed to be associated with the abnormal photocurrent. Further optoelectronic measurements with the defect density tuned unveiled that the interaction between the defects and domain walls is essential to give a rise to a large photocurrent in BiFeO3 thin films. The study reveals a novel domain‐wall‐defect photovoltaic effect and provides a simple thermal annealing‐treatment strategy to boost the photocurrents and power output by several folds. Abstract : The effects of oxygen vacancy and domain wall on the photocurrent of BiFeO3 thin films are studied by the authors. They reveal that simple thermal annealing treatments could improve the photocurrent by orders of magnitude attributed to an interaction between the domain wall and defects. This study paves a way for the development of domain‐wall‐engineered photovoltaic devices.